2010
DOI: 10.4314/dmsj.v14i1.51189
|View full text |Cite
|
Sign up to set email alerts
|

Effects of infections on severely malnourished children in Kilifi-Mombasa and Dar es Salaam: a comparative study.

Abstract: To determine the e ects of infections on severely malnourished children. Study design: Descriptive, cross-sectional hospital based study. Results: There is little di erence in the prevalence of severe malnutrition between the two hospitals. 55% of all malnourished children were boys. Nonoedematous Protein Energy Malnutrition was more prevalent at Muhimbili National Hospital than at Kili District Hospital. More than 75% of all severe Protein Energy Malnutrition patients were below two years of age, 36% of all s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
3
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 4 publications
1
7
3
1
Order By: Relevance
“…A previous Indian study [8] showed only 3.8% of children with past history of measles but we found a higher proportion. Malaria and HIV infection were previously reported as major co-morbidities with total prevalence of 21% and 29.2%, respectively [21] but In our study malaria, HIV were not found to be as comorbid condition.…”
Section: Discussioncontrasting
confidence: 73%
“…A previous Indian study [8] showed only 3.8% of children with past history of measles but we found a higher proportion. Malaria and HIV infection were previously reported as major co-morbidities with total prevalence of 21% and 29.2%, respectively [21] but In our study malaria, HIV were not found to be as comorbid condition.…”
Section: Discussioncontrasting
confidence: 73%
“…However, there are also studies that report greater social valorization of sons at the detriment of daughters [ 19 ], including dietary discrimination [ 20 ], thereby dispelling conclusions of a nutritionally advantaged position of female over male children. Other reasons could be that boys were more influenced by environmental stress than girls [ 20 , 21 ]. There were significant age differences in stunting in that a higher proportion of the two and three year olds compared to one, four and five year olds were stunted.…”
Section: Discussionmentioning
confidence: 99%
“…Abrupt weaning and lack of breast feeding contribute to malnutrition in the first year of life, while inadequate intake of protein and calories in the second year of life [5]. In developing countries, malnutrition contributes to more than 50 % of under-five mortality [6][7][8][9]. Malnourished survivors are usually left with mental developmental delay, poor school performance and reduced intellectual achievements [2,6,10].…”
Section: Introductionmentioning
confidence: 99%
“…In developing countries, malnutrition contributes to more than 50 % of under-five mortality [6][7][8][9]. Malnourished survivors are usually left with mental developmental delay, poor school performance and reduced intellectual achievements [2,6,10].…”
Section: Introductionmentioning
confidence: 99%